Manajemen Pengelolaan Pemesanan dan Penjualan Produk Secara Online Menggunakan Metode Real Time Processing - Sri Handoko; Hendri Rasminto (UNIVERSITAS STEKOM, 2020)
This study aims to design an ordering and sales information system at CV New Flashphone Semarang. Through the creation of the Ordering and Sales Information System, it is expected to be able to simplify the process of ordering and selling goods, as well as to make reports of goods more quickly, which is used by the company as a management tool in sales activities at CV New Flashphone Semarang. The research method used is the Real Time Processing research method, which is one of the processing with concrete processes that uses online media. This input is done continuously and can automatically be obtained through the sensor. In using this real time processing, the user gets much more benefit because the time it takes to get the results is instant. So you don't have to wait long to get the desired result. The reaction is much faster than some of the previous processing. The results of the research from the design of ordering and sales information systems are to make it easier for consumers to make purchases and order goods, as well as to facilitate companies in marketing their products and also make it easier for companies to control existing goods. Currently the company is still using a manual system in recording ordering transactions and selling goods, even though implementing an information system will minimize the risk of recording errors in reports, so that information is faster and more complete.